Development of an Asset Management Framework for the Oil and Gas Industry - Baswaid, Ahmed Mohsen Salem (Curtin University, 2019)
The objective of this thesis is to improve asset management performance through the development of an oil and gas-specific asset management framework. This objective is crucial, given that there is currently little empirical data about asset management. This study encompasses a qualitative methodology, including purposive sampling of fifty employees employed by three organizations. The findings revealed five key challenges that have been hindering a smooth application of asset management within the oil and gas industry.